Carbonate Reduction and the Properties and Applications of Carbon Formed Through Electrochemical Deposition in Molten Carbonates: A Review. (10th September 2015) - Hughes, Matthew A.; Allen, Jessica A.; Donne, Scott W.
Abstract: The electrochemical conversion of CO2 to carbon through the reductive electrolysis of molten carbonate-containing salts has been studied by a range of groups. These groups have examined the yields, mechanisms of deposition and physical characteristics of carbon synthesized through electrolysis using a variety of electrolytes, substrates, temperatures, current densities and deposition potentials. The findings of these research groups have been compiled and compared, with particular significance being placed on findings relating to the influence of variables on the physical properties of carbon obtained in this manner. Research on potential applications of carbon derived from the electrolysis of molten carbonate-containing salts has been presented and the energetics of these carbons have been discussed. The possibility of using this form of carbon synthesis as a manner of permanent waste CO2 sequestration has been considered.